Understanding calcium waves and sparks in central neurons - Ross, William N. (Nat Rev Neurosci, 2012)
All cells use changes in intracellular calcium concentration ([Ca(2+)](i)) to regulate cell signalling events. In neurons, with their elaborate dendritic and axonal arborizations, there are clear examples of both localized and widespread Ca(2+) signals. [Ca(2+)](i) changes that are generated by Ca(2+) entry through voltage- and ligand-gated channels are the best characterized. In addition, the release of Ca(2+) from intracellular stores can result in increased [Ca(2+)](i); the signals that trigger this release have been less well-studied, in part because they are not usually associated with specific changes in membrane potential. However, recent experiments have revealed dramatic widespread Ca(2+) waves and localized spark-like events, particularly in dendrites. Here we review emerging data on the nature of these signals and their functions.